2008
DOI: 10.1007/s00404-008-0818-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of amniotomy and immediate oxytocin infusion versus amniotomy and delayed oxytocin infusion for induction of labour at term

Abstract: In induction of labour at term, amniotomy and immediate oxytocin infusion is associated with the establishment of active labour at 4 h, a shorter amniotomy-delivery interval and greater maternal satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…There was no control group in two other studies (Cummiskey 1989; Xenakis 1995). Two trials were for induction labour, not augmentation (Gagnon-Gervais 2011; Selo-Ojeme 2009). Finally, in one study (Verkuyl 1986), there was no information on the inclusion or exclusion characteristics of the women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no control group in two other studies (Cummiskey 1989; Xenakis 1995). Two trials were for induction labour, not augmentation (Gagnon-Gervais 2011; Selo-Ojeme 2009). Finally, in one study (Verkuyl 1986), there was no information on the inclusion or exclusion characteristics of the women.…”
Section: Resultsmentioning
confidence: 99%
“…There was no control group Ruiz Ortiz 1991 Method of distribution between experimental group and control group are not mentioned. No randomization Selo-Ojeme 2009 It is for induction labour, not augmentation. Verkuyl 1986 No information on inclusion or exclusion criteria. Xenakis 1995 Low-dose versus high-dose oxytocin augmentation of labour.No control group. …”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…In literature there is no clear indication about which of the two interventions should precede the other. Different studies report that early or late oxytocin administration after rupture of membranes reduce labour duration, thus favouring vaginal delivery (23). Other studies established there is no real difference in clinical outcomes between oxytocin administration with ruptured or intact membranes (24).…”
Section: Discussionmentioning
confidence: 99%
“…The immediate versus delayed use of an oxytocin infusion after amniotomy for the purpose of IOL was compared in a small randomised controlled trial (RCT) in 2009. The likelihood of being in established labour 4 hours after amniotomy, and having a shorter amniotomy‐to‐delivery interval, was higher in the immediate infusion group . A more recent RCT compared immediate and delayed (4 hours) oxytocin use in parous women and found that both options were reasonable, thus the decision should be based on local resources and maternal choice …”
Section: Common Methods For Induction Of Labourmentioning
confidence: 99%